Structural mass spectrometry comes of age: new insight into protein structure, function and interactions. (15th January 2019) - Allison, Timothy M.; Bechara, Cherine
Abstract : Mass spectrometry (MS) provides an impressive array of information about the structure, function and interactions of proteins. In recent years, many new developments have been in the field of native MS and these exemplify a new coming of age of this field. In this mini review, we connect the latest methodological and instrumental developments in native MS to the new insights these have enabled. We highlight the prominence of an increasingly common strategy of using hybrid approaches, where multiple MS-based techniques are used in combination, and integrative approaches, where MS is used alongside other techniques such as ion-mobility spectrometry. We also review how the emergence of a native top-down approach, which combines native MS with top-down proteomics into a single experiment, is the pièce de résistance of structural mass spectrometry's coming of age. Finally, we outline key developments that have enabled membrane protein native MS to shift from being extremely challenging to routine, and how this technique is uncovering inaccessible details of membrane protein–lipid interactions.